CNKSR2-related neurodevelopmental and epilepsy disorder: a cohort of 13 new families and literature review indicating a predominance of loss of function pathogenic variants - Leigh Ann Higa; Jennifer Wardley; Christopher Wardley; Susan Singh; Timothy Foster; Joseph J. Shen (BMC, 2021)
Abstract Background Pathogenic variants in connector enhancer of kinase suppressor of Ras-2 (CNKSR2) located on the X chromosome (Xp22.12) lead to a disorder characterized by developmental delay and a characteristic seizure phenotype. To date, 20 affected males representing 13 different pathogenic variants have been published. Case presentation We identified an 8-year-old male with seizures, abnormal electroencephalogram (EEG) with epileptiform abnormalities in the right hemisphere, and developmental delay with notable loss of speech following seizure onset. Additional concerns include multiple nighttime awakenings, hyperactivity, and autism spectrum disorder. Genetic testing identified a de novo pathogenic nonsense variant in CNKSR2. Through an active family support group, an additional 12 males are described, each harboring a different CNKSR2 variant. The clinical presentation and natural history consistently show early developmental delay, sleep disturbances, and seizure onset in childhood that is initially intractable but later becomes better controlled. Virtually all of the pathogenic variants are predicted to be loss of function, including genomic deletions, nonsense variants, splice site mutations, and small insertions or deletions. Conclusions This expanded knowledge, combined with functional studies and work with animal models currently underway, will enable a better understanding and improved ability to care for individuals with CNKSR2-related neurodevelopmental and epilepsy disorder.